Uniformly Dispersed Ru Nanoparticles Constructed by In Situ Confined Polymerization of Ionic Liquids for the Electrocatalytic Hydrogen Evolution Reaction. Issue 7 (18th June 2021) - Zhang, Yong‐Ya; Zhang, Nan; Peng, Peng; Wang, Rui; Jin, Yan; Lv, Ya‐Kun; Wang, Xin; Wei, Wei; Zang, Shuang‐Quan
Abstract: Design and development of cost‐effective electrocatalysts with high efficiency and stability for scalable and sustainable hydrogen production through water splitting is still challenging. Herein, with the aid of divinyl functionalized ionic liquids, uniformly distributed Ru nanoparticles (NPs) on nitrogen‐doped carbon frameworks are obtained via an in situ confined polymerization strategy. Attributed to the unique lamellar structure and confinement effect of carbon supports, the optimized homo‐PIL‐Ru/C‐600 (with Ru 10 wt%) catalyst exhibits superior catalytic efficiency for the hydrogen evolution reaction with the overpotential of only 16 mV at a current density of 10 mA cm −2 and the corresponding Tafel slope of only 42 mV dec −1 . Moreover, the performance can be well reserved even after 10 000 cycles, demonstrating excellent stability and promising potentials for industrial application. This work not only provides a facile approach for the preparation of highly efficient Ru‐based catalysts, but also guides the synthesis of other highly dispersed metallic NPs for special applications. Abstract : Commonly, it is difficult for metal salts to form highly dispersed metal active‐sites on a carbon matrix due to the limitation of the heterogeneous system. In this work, a novel approach is developed to prepare uniformly dispersed metal‐based nanocatalysts with ionic liquids as solvents and support precursors by in situ confined polymerization.